Sugar beet : A competitive innovation - Huyghe, Christian; Desprez, Bruno; Laudinat, Vincent; Huyghe, Christian; Desprez, Bruno; Laudinat, Vincent (éditions Quae, 2020)
Sugar beet has entered the age of liberalism with the abolition of production quotas in Europe. It finds itself on the world market and on an equal footing with sugar cane. France has benefited from the AKER - Sugar beet 2020, a competitive innovation Investments for the Future Programme, which aims to double the annual growth rate of the sugar yield per hectare of beet. It has made a scientific breakthrough by researching all of the genetic diversity available worldwide, and by carrying out genotyping before phenotyping. It is developing new genetic material, available for introduction into future sugar beet varieties. It also offers innovative tools and methods in the fields of genotyping and phenotyping, supporting players in the sector - beet growers and sugar manufacturers - in their imperative improvement in competitiveness. This book is mainly intended for scientists and professionals, and all those interested in research, development and training in the plant sector. It has just completed eight years of multidisciplinary work bringing together a hundred scientists. The AKER programme puts for a long time sugar beet in the top tier of cultivated species and helps to provide the consumer with quality sugar produced locally and under environmentally friendly conditions.
English
Keywords: Technology, engineering, agriculture; agronomy; sugar beet